Effectiveness seed age to growth and production (Oryza sativa l.) on hazton system. Issue 1 (March 2021) - Ramli,; Bahrun,; Rafiuddin,
Abstract: This study aims to determine the effect of seed age on the growth and production of rice in the Hazton system. The study method was arranged based on Plot Design, consisting of 2 treatments and four replications so that eight plots obtained. The result of T- test analysis showed that seed treatment 26 days after distribution gave significant effect to plant height 100, 8 cm, the number of tiller 41, 45 in each tiller, productive panicle 29, 6 panicles, panicle length 25, 8 cm, production Weight of dry unhulled rice 8.47 ton/ha and weight of dry milled grain 7.44 ton /ha.